ІНСТИТУЦІЙНІ ПЕРЕТВОРЕННЯ В СИСТЕМІ ДЕРЖАВНОГО УПРАВЛІННЯ ЗЕМЕЛЬНИМИ РЕСУРСАМИ (International Journal of Innovative Technologies in Economy, 2018)
Today one of the problems is the fact that a significant part of the management team of different levels of government management is not well acquainted with the real state of the economy of the country and the necessity of its urgent reforming, which objectively impedes the transition to a new, more progressive, model of management of the country. Thus, a well- grounded judgment those radical changes in human resources policy have long been on time.The scientific and theoretical aspects of the infrastructure restructuring of Ukraine’s economy, its structural elements and institutional ways of state management of land resources are researched in the article. General tendencies of decreasing of economic indicators in the most significant spheres of economy of the country, including the land one, are investigated on the basis of the continuation of the destructive influence of crisis phenomena due to the global financial crisis.It is pointed out the importance of a radical change of the vector of the investment policy of the state from the passive and expectation one to the dynamically active one, which will give the opportunity to obtain modern technologies that are extremely necessary today, taking into account the miserable state of science in the state